Determinants of suicidal behaviour in Malaysia - Cheah, Yong Kang; Omar, Mohd Azahadi; Phang, Siew Nooi; Abd. Manaf, Noor Hazilah (Malaysian Economic Association, 2018)
A sharp rise in the prevalence of suicide has become a serious public health concern. Acquiring a better understanding of the determinants of suicidal behaviour can help to implement a more effective policy directed towards reducing the suicide rate. In this study, we attempt to examine the effects of sociodemographic, lifestyle and health factors on suicidal behaviour among Malaysian adults. A rigorous statistical method and a nationally representative data are used for analyses. We find that age, gender, race, marital status, self-rated health, diabetes and hypercholesterolemia are significantly associated with suicidal behaviour. Specifically, there are positive relationships between the likelihoods of engaging in suicidal behaviour and young adults, females, Indians/others, being unmarried, and having poor health conditions. We conclude that sociodemographic and health factors play an important role in affecting suicidal behaviour, whereas lifestyle factor does not. As an intervention measure towards overcoming the problem of high suicide rate, effective policies should be targeted at individuals who are likely to engage in suicidal behaviour